2012
DOI: 10.1080/09593330.2012.705895
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of trihalomethane and haloacetic acid formation from natural organic matter surrogates

Abstract: Disinfection by-products (DBPs) in drinking water, including trihalomethanes (THMs) and haloacetic acids (HAAs), arise from reactions of natural organic matter (NOM) with chlorine and other disinfectants. The objective of this review was to investigate relationships between the molecular properties of NOM surrogates and DBP formation using data collated for 185 compounds. While formation of THMs correlated strongly with chlorine substitution, no meaningful relationships existed between compound physicochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(90 citation statements)
references
References 56 publications
6
83
0
1
Order By: Relevance
“…The concentration may vary according to many factors such as topography, season, flood, drought and human activities (Hudson et al, 2007;Abdullah et al, 2003). This indicated that, NOM concentration and characteristics is dependent to water origin and its surrounding (Bond et al, 2012;Zularisam et al, 2006). Table 1 shows variation in hydrophobic and hydrophilic concentration in river water at different places.…”
Section: Natural Organic Matter Characteristicsmentioning
confidence: 99%
“…The concentration may vary according to many factors such as topography, season, flood, drought and human activities (Hudson et al, 2007;Abdullah et al, 2003). This indicated that, NOM concentration and characteristics is dependent to water origin and its surrounding (Bond et al, 2012;Zularisam et al, 2006). Table 1 shows variation in hydrophobic and hydrophilic concentration in river water at different places.…”
Section: Natural Organic Matter Characteristicsmentioning
confidence: 99%
“…The maturation of municipal water purification in the last decades has authorized cities in the developed countries to be mostly without of waterborne diseases. Since the application of filtration and disinfection of potable water in the United States, waterborne diseases like cholera and typhoid have been almost removed (Bond et al, 2012;Weiner, 2012;Gopal et al, 2007;Liviac et al, 2011;Ghernaout et al, 2008;.…”
Section: Introductionmentioning
confidence: 99%
“…The total concentration of these four THMs (Total THMs) is regulated and should not exceed the maximum contaminant level (MCL) of 0.080 mg·L ) [2,3] in finished drinking water. Data from the Environmental Working Group Drinking Water Database collected in 2007 [5] demonstrates that one in five legal violations in drinking water is a violation of the MCL for Total THMs. Clearly, many utilities struggle each year to meet these regulations and the occurrence of THMs formation in public drinking water is widespread.…”
Section: Introductionmentioning
confidence: 99%
“…This is due in no small part to water chlorination which many consider the most significant public health development of the 20th century [1]. Unfortunately, despite all its benefits, water chlorination results in the formation of carcinogenic disinfection by-products (DBPs) from the reactions of free available chlorine with natural organic matter in source waters [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation